2015
DOI: 10.1007/s00586-015-3910-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of observational studies reveals no association between low back pain and lumbar spondylolysis with or without isthmic spondylolisthesis

Abstract: There is no strong or consistent association between SL/IS and LBP in epidemiological studies of the general adult population that would support a hypothesis of causation. It is possible that SL/IS coexist with LBP, and observed effects of surgery and other treatment modalities are primarily due to benign natural history and nonspecific treatment effects. We conclude that traditional surgical practice for the adult general population, in which SL/IS is assumed to be the cause of non-radicular LBP whenever the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Recently, a systematic review found that there was no strong or consistent association between IS and LBP in epidemiological studies of the general adult population. 26 The current study demonstrated that the surgical treatment of the involved vertebral segment effectively improved LBP regardless of whether an autologous graft or a cage was used for PLIF. A previous study reported that anterior lumbar interbody fusion was beneficial for LBP improvement for IS.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, a systematic review found that there was no strong or consistent association between IS and LBP in epidemiological studies of the general adult population. 26 The current study demonstrated that the surgical treatment of the involved vertebral segment effectively improved LBP regardless of whether an autologous graft or a cage was used for PLIF. A previous study reported that anterior lumbar interbody fusion was beneficial for LBP improvement for IS.…”
Section: Discussionmentioning
confidence: 60%
“…In other words, the symptoms of patients enrolled in this study were considered to be unrelated to the presence of spondylolysis. Although most patients with spondylolysis are asymptomatic, 8 they may present with low back pain. 23 , 24 When the origin of the pain is obvious, direct repair of the pars defect is an effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that most cases of lumbar spondylolysis are asymptomatic 8 , 9 and that minimally invasive decompression is associated with less slip progression in patients with degenerative spondylolisthesis, 10 we speculated whether surgery to repair spondylolysis may be unnecessary in patients with apparent disc herniation and sciatica. Microendoscopic discectomy (MED) is a minimally invasive technique for LDH that preserves posterior supporting muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Activity modification, bracing, and core-strengthening exercises alone may not be the most appropriate treatment for athletes from EB LBP. Mounting evidence 41 indicated that the pain from EB LBP may in fact not be from a pars interarticularis defect. Learning how to control lumbar extension with sport-specific movements and understanding pain may lead to more effective and efficient recovery in these athletes.…”
Section: Discussionmentioning
confidence: 99%